A transformative approach to social work education - Dhungel, Rita; Lorenzetti, Liza; Lorenzetti, Diane; Oshchepkova, Tatiana; Haile, Lemlem (My University, 2017)
The paper presents an overview of “The Journey Guides Program” - a mentorship and experiential learning framework developed by the Faculty of Social Work, University of Calgary in Canada. This program was implemented in an Advanced Graduate Seminar, a preparatory course for graduate Social Work students prior to entering their field placements. The purpose of this program is to advance practice-based knowledge in transformative learning. This article begins by discussing critical pedagogy, the theoretical framework that underpinned “The Journey Guides Program”, followed by a description of the eight-step process the authors adopted to implement this program. This paper concludes by presenting our evaluation plan and subsequent steps.
Presented on June 21-23, 2017, at the "3rd International Conference on Higher Education Advances (HEAd’17) held at the Universitat Politècnica de València (UPV) in Valencia, Spain.
Keywords: journey guides; transformative learning; mentorship; social work